Comparison between collateral status and DEFUSE 3 or DAWN criteria in patient selection for endovascular thrombectomy within 6−24 hours after stroke: a protocol for meta-analysis - Yun Chen; Mao Li; Dongdong Yang; Junyan Liu; Yuling Shen; Shanyu Liu (BMJ Open, 2022)
Introduction Perfusion imaging according to the DEFUSE 3 or DAWN criteria has been applied to select patients with large vascular occlusive stroke undergo endovascular therapy (EVT) in the extended time window. Emerging studies have shown that collateral blood flow-based criteria may be as effective as DEFUSE 3 and DAWN criteria for the evaluation of EVT eligibility beyond 6 hours. We will conduct a meta-analysis to compare collateral status-based criteria with DEFUSE 3 or DAWN criteria.Methods and analysis We will conduct a search for the studies comparing collateral blood flow-based imaging with CT perfusion using the DEFUSE 3 or DAWN criteria in selecting patients with acute ischaemic stroke undergo EVT in the Web of Science, PubMed, EMBASE and the Cochrane Library databases between November 2017 and November 2021. We will also search the sources of grey literature, the reference lists of included studies and the newly published studies during the review period. Two investigators will independently screen the eligible studies and extract data. The study quality will be assessed by using the Newcastle-Ottawa Scale or the Cochrane risk bias tool. Stata V.17 will be used to conduct data analysis.Ethics and dissemination Patient informed consent and ethics approval are not necessary as this study uses only published studies. The finding of this meta-analysis will be propagated through committee conferences or peer-reviewed journals.PROSPERO registration number CRD42021281928.